Assessment of the Relationship Between Anterior Teeth Colour and Skin Colour by assessing different measurement tools in Adult Patients: A Systematic Review - Moazam, Ryhana H; AL-Rawas, Matheel; Ab-Ghani, Zuryati; Ahmad, Wan MAW; Halim, Mohamad S; Bin Jamayet, Nafij; Abdullah, Johari Y (Journal of Baghdad College of Dentistry, 2024)
Background: Previous research conducted since 1968 have extensively examined the correlation between tooth color and skin color. The purpose of these studies was to determine whether skin color could effectively influence dentists in choosing tooth color. The objective of this systematic review is to examine the methodologies employed in assessing the relationship between tooth and skin color, and to identify the most precise and dependable approaches for modeling and evaluating this relationship. The systematic review was registered in the PROSPERO (CRD42022356022). This systematic review was done on four databases using PRISMA 2009 search strategy, and selected studies were chosen according to PICO model. JBI Critical Appraisal Checklist was used for quality assessment. Out of 1611 articles that were found in the databases, 10 articles matched the criteria and were selected for this systematic review study. Three main methods were found in the 10 studies: conventional methods, digital methods, conventional-digital (mixed) methods. Digital methods were found to be the more reliable methods for color evaluation. Specific settings should be applied during digital color measuring methods.  Conventional and digital assessment methods showed either a negative or a positive significant association between the color of teeth and skin. However, the combined method (digital for tooth and visual for skin) did not show any such relation. It is imperative to conduct and apply research in Artificial Intelligence to forecast tooth color based on knowledge of skin color.